MILK PRODUCTIVITY INDICATORS OF GOATS OF ZAANEN BREED BROUGHT FROM ABROAD ACCORDING TO CONSTITUTIONAL TYPE IN THE CONDITIONS OF KARAKALPAKSTAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In this article, the indicators of milk productivity in the first lactation of imported Zaanen goats bred in the conditions of Karakalpakstan were studied for the first time.